جهود العلماء والمؤسسات التعليمية في نشر الإسلام والسلام في فطاني =Efforts of Muslim Religious Scholars and Educational Institutions to Spread Islam and Peace in Patani =Usaha Ulama dan Institusi Pengajian di Dalam Menyebarkan Islam - Laeba, Muhammad (IIUM, 2010)
In this study, the researcher tries to give the historical background about the entry of Islam as well as past and present political situations in the region of Patani. At the same time, he also points out the role of Muslim religious scholars in spreading Islam and establishing peace in the region. Those are the people whose names remained rooted in the minds of the Muslims in Thailand despite attempts were made to delete their identities. The study also comprises of the role of educational institutions (such as Ma‘aarifat National School founded by Sheikh Solong, institutions founded by Sheikh Lampung and Jala Islamic University founded by Dr. Ismail Lutfi) in spreading Islam and establishing peace in the region at the present time. The research is divided into three sections: first section addresses the past and present political situation in the state of Patani; while the second section deals with the role of Muslim religious scholars in spreading Islam and establishing peace in Patani with some examples of Patani scholars who had a great influence in spreading Islam and establishing peace in the region. In the third section, the researcher tries to discuss the role of educational institutions in spreading Islam and establishing peace in Patani.